2019
DOI: 10.2174/1568026619666190723153925
|View full text |Cite
|
Sign up to set email alerts
|

Plants and Phytocompounds Active Against Bothrops Venoms

Abstract: : Snakebite envenomation is an important health problem in tropical countries, with severe human and social consequences. In Latin America, the Bothrops species constitute the main threat to humans, and the envenomation caused by these species quickly develops into severe local tissue damage, including swelling, hemorrhaging, myonecrosis, skin ulceration, and pain. The systemic effects of envenomation are usually neutralized by antivenom serum therapy, despite its intrinsic risks. However, neutralization of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 119 publications
0
6
0
Order By: Relevance
“…In this study, B. xbuttiana Orange was able to reduce proteolytic activity and PLA2. Distinct studies have shown that bioactive compounds from plants have significant inhibitory properties against snake venom enzymatic toxins such as PLA2 and hyaluronidases (Santhosh et al, 2013;Jorge et al, 2019). However, these compounds may be responsible for inhibition of toxins present in snake venom, acting directly as enzymatic inhibitors and chemical inactivators, or indirectly as immunomodulators, by interacting with biological targets (Santhosh et al, 2013;Jorge et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, B. xbuttiana Orange was able to reduce proteolytic activity and PLA2. Distinct studies have shown that bioactive compounds from plants have significant inhibitory properties against snake venom enzymatic toxins such as PLA2 and hyaluronidases (Santhosh et al, 2013;Jorge et al, 2019). However, these compounds may be responsible for inhibition of toxins present in snake venom, acting directly as enzymatic inhibitors and chemical inactivators, or indirectly as immunomodulators, by interacting with biological targets (Santhosh et al, 2013;Jorge et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…There are many investigations reporting the use of plants with antiophidic properties. A considerable number of studies have described immunomodulatory properties in various medicinal plants (Jorge et al, 2019). Some plants are able to inhibit both cellular and humoral responses, while others are capable of stimulating the immune response.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beatriz Cardoso Roriz; Gabriela Ramos Cerqueira; Susana Elisa Moreno study conducted with the Malvaceae family, the leaves of the species Abutilon theophrasti have compounds with anti-inflammatory action. Since in the snakebite accident, especially caused by Bothrops snakes, responsible for most cases of poisoning, the inflammatory response is responsible for the damage caused by the poison (JORGE et al, 2019).…”
Section: Discussionmentioning
confidence: 99%